Penerapan Kompres Hangat Daun Kelor Terhadap Nyeri Asam Urat pada Lansia di Desa Pucangsawit - Yulia Dwi Pratiwi; Irma Mustikasari (PPNI UNIMMAN, 2024)
Background: The elderly are more likely to suffer from gout with symptoms of pain and swelling in the joints. Pain that is not handled properly can trigger a prolonged stress response, which will reduce the body's resistance. One non-pharmacological therapy that can be given to gout sufferers is a warm compress from Moringa leaves. Warm compresses from Moringa leaves are a technique for applying compresses to joint areas that experience pain due to gout. Objective: To determine the results of differences in pain intensity before and after applying a warm Moringa leaf compress to Lanisa. Method: This research used a descriptive research design with a case study approach on 2 respondents in Pucangsawit Village, Jebres, Surakarta who experienced joint pain due to gout, carried out once every morning for 3 consecutive days within 20 minutes. Results: there was a decrease in the intensity of gout pain after giving therapy to Mrs. Y from a pain scale of 6 to a pain scale of 3 and in Mrs. M from a pain scale of 5 to a pain scale of 2. Conclusion: the application showed that after applying a warm compress on Moringa leaves there was a change in the intensity of pain in both respondents.